Community Power and People’s Participation in Tourism Management according to the Way of Life of the Community in Bueng Lahan Area, Chatturat District, Chaiyaphum Province - Mamuang, Phaitoon (Academic MCU Buriram Journal, 2023)
The purpose of this research were: 1) to study public opinions towards the process. 2) a study of community power in managing community-based tourist attractions in Bueng Lahan, Chatturat District, Chaiyaphum Province, and 3) a study of the approaches for enhancing community power in managing community-based tourist attractions in Bueng Lahan, Chattra District, Chaiyaphum Province. It is an integrated research method. between quantitative and qualitative research There are research tools which are questionnaires and interview forms. There was a sample group of 400 people at a level of error of 0.05 and random sampling was convenient. and the target group of 30 people from a specific selection Data were analyzed using statistics, percentage, mean, and standard deviation. and content analysis The research results found that: 1. The level of people’s opinions towards the process of public participation in the management of tourist attractions according to the community way in Bueng Lahan District, Chatturat District, Chaiyaphum Province. Bueng Lahan was at a high level (= 4.42). was at a high level (= 4.41). in the management of Bueng Lahan tourist attractions at a high level ( = 4.39) 2. Community power in managing tourist attractions according to the community way of life in Bueng Lahan, Chatturat District, Chaiyaphum Province, is the management of allocating space for boarding boats to see the red lotus field. Collect the fee for getting on the boat to see Bua Daeng. collecting fees to see the wooden bridge The kiosks for the members of the environmental management group are organized together in the community. 3. Guidelines for enhancing community power in managing tourist attractions according to the community way of life in Bueng Lahan, Chatturat District, Chaiyaphum Province, namely the enhancement of community and area potential. Creation of community identity in tourist attraction management Promotion of public participation process Promoting the creation of community networks Promote tourist attraction enterprises in setting up a learning center for conservation tourism and the application of Saraniyadhamma principles.